Livro-reportagem: uma proposta de criação de perfis de artistas paraibanos a partir do jornalismo literário - Santos, Cibelly Correia dos (2016)
This project aims to create a creative nonfiction book that will have profile stories of artists from the Brazilian state of Paraíba, and that will be achieved through narratives of Literary Journalism. Because of the new technologies and the unstoppable flow of information, the majority of daily news is superficial and direct, which makes it hard deepening the subjects they refer to. Literary Journalism in the other hand puts together techniques from journalism and literature, as procedures of observation, description and narrative, in order to humanize as much as possible the reports and give cadence to the text. It‘s noticeable that news based on Literary Journalism is related to cultural events or press releases sent by media offices. That makes it difficult for society to have a clear idea of its own culture and knowledge about its own artists. Therefore, the creative nonfiction book purposed in this project will contain six profile stories of artists from Paraíba with established careers in many segments, willing to show their personal lives and production over the years as well as the historic and cultural context in which they have been involved. The option for a creative nonfiction book is due to the fact it is a tool that allows journalists to write deep reports with deeper investigation and also freedom on the narrative stylistics.